Decision Making and Oddball Effects on Pupil Size: Evidence for a Sequential Process - Strauch, Christoph (J Cogn, 2020)
In our physical environment as well as in many experimental paradigms, we need to decide whether an occurring stimulus is relevant to us or not; further, stimuli have uneven probabilities to emerge. Both, decision making and the difference between rare and frequent stimuli (oddball effect) are described to affect pupil dilation. Surprisingly though, conjoint systematic pupillometric investigations into both factors are still rare. In two experiments, both factors as well as their interplay were investigated. Participants completed a sequential letter matching task. In this task, stimulus probability and letter matching (decision making) were manipulated independently. As dependent variables, pupil dilation and reaction time were assessed. Results suggest a clearly larger pupil dilation for target than for distractor letters, even when targets were frequent and distractors rare. When considering the data structure best, no main effect of stimulus probability was found, instead, oddball effects only emerged when stimuli were goal-relevant to participants. The results are discussed in the light of common theoretical concepts of decision making and stimulus probability. Finally, relating theories of each factor, we propose an integrated framework for effects of decision making and stimulus features on pupil dilation. We assume a sequential mechanism during which incoming stimuli are decided upon regarding their goal relevance and, about 200 ms later, relevant stimuli are appraised regarding their value.